SUSTAINABLE URBAN COMMUNITY DEVELOPMENT THROUGH AGENDA 21 - Zainal Md Zan; Kamarudin Ngah; Azlizan Talib (Journal of Techno-Social, 2015)
The much-talked about issues such as the rising of heavy crime cases, problems in solid waste management, air and water pollution as well as traffic congestion detering the quality of life among urban community members. Urgent and proactive measure is highly desireable in order to preserve and maintain the integral parts of urban’s higher quality of life. All parties should take part in ongoing efforts to achieve sustainable development through various means. Local Agenda 21 (LA21) serves as one of the efforts in achieveing the ultimate goal of sustainable development through better collaboration and cooperation among stakeholders including local government, non-governmental organisations and the community at large. The core principle of the LA21 program lies in the spirit of cooperation among community members, local authorities and the private sectors. This could be achieved through various activities including from the beginning such as through a comprehensive planning for the local area to achieve the sustainable development. Community members should be involved in brainstorming of the ideas and expressing their views so that authorities would be able to identify the real and arising issues in the community. Through this way a sustainable town and municipal planning could be developed and initiated. This paper discusses the importance of urban community participation in achieving sustainable development as practiced through LA21 in Seberang Perai Municipal Council, Penang.